Convergence of adaptive finite element methods for eigenvalue problems - Garau, Eduardo Mario (2009)
In this paper we prove convergence of adaptive finite element methods for second-order elliptic eigenvalue problems. We consider Lagrange finite elements of any degree and prove convergence for simple as well as multiple eigenvalues under a minimal refinement of marked elements, for all reasonable marking strategies, and starting from any initial triangulation.